Предмет: Математика,
автор: krisshmis
Спростіть вираз 2(5х-6)-3(2х-3) =
Ответы
Автор ответа:
0
Ответ:
Буде 4х - 3
Пошаговое объяснение:
2(5х - 6) - 3(2х - 3) = 10х - 12 - 6х + 9 = 4х - 3
Автор ответа:
0
Ответ:
4x - 3
Пошаговое объяснение:
2 (5x - 6) - 3 (2x - 3)
10x - 12 - 3 (2x - 3)
10x - 12 - 3 (2x - 3)
10x = 12 - 6x + 9
4x - 3
Похожие вопросы
Предмет: Українська мова,
автор: krinsh8
Предмет: Биология,
автор: aleksapankova04
Предмет: Английский язык,
автор: akimenkoangelina076
Предмет: Қазақ тiлi,
автор: syrlybekovazarina8